Comparison of crash behaviour prediction of a car crash box using initial and updated finite element model - N. A. Z., Abdullah; M. S. M., Sani; Salwani, Mohd Salleh (IOP Publishing, 2019)
Topic of crashworthiness is gaining popularity as vehicle safety is becoming main concern to the vehicle manufacturers worldwide. Due to this factor, energy absorbing members on vehicle such as crash box is researched by many which lead to various strategies of design optimization has been carried out in order to seek a good energy absorber on vehicle. Among the popular method of determining the crash performance of a structure is by using dynamic analysis in computational finite element model (FEM). However, since finite element analysis (FEA) is only an approximation method which in many cases can be less reliable, model updating method is often suggested to improve its reliability. This study seeks to investigate the crash behaviour of initial and updated crash box model. The velocity of impactor, the deformation, collapse distance and energy transferred to the two models of crash box are compared. The findings show that the initial and updated model of the crash box in this study, do have different crash behaviour. However, the difference level is relatively small. The investigation on the method of validation for the updated model in terms of crash behaviour is highly recommended.